Calpain-Mediated Cleavage of Calcineurin in Puromycin Aminonucleoside-Induced Podocyte Injury - Ding, Fangrui; Li, Xuejuan; Li, Baihong; Guo, Jifan; Zhang, Yanqin; Ding, Jie (PloS one, 2016)
The calcineurin inhibitors cyclosporine A (CsA) and tacrolimus are widely used in the treatment of proteinuria diseases. As the direct target of these drugs, calcineurin has previously been demonstrated to play a role in proteinuria diseases. However, aside from its immune-related effects, the local status of calcineurin in renal inherent cells has not been fully explored in the settings of proteinuria disease and podocyte injury. In this study, calcineurin activity and protein expression in the well-known puromycin aminonucleoside (PAN)-induced podocyte injury model were examined. Interestingly, we found that calcineurin activity was abnormally increased in PAN-treated podocytes, whereas the expression of the full-length 60-kDa calcineurin protein was decreased. This result suggests that there may be another activated form of calcineurin that is independent of the full-length phosphatase. To investigate whether calpain is involved in regulating calcineurin, we exposed PAN-treated podocytes to both pharmacological inhibitors of calpain and specific siRNAs against calpain. Calpain blockade reduced the enhanced calcineurin activity and restored the down-regulated expression of 60-kDa calcineurin. In addition, purified calpain protein was incubated with podocyte extracts, and a 45-kDa fragment of calcineurin was identified; this finding was confirmed in PAN-induced podocyte injury and calpain inhibition experiments. We conclude that calcineurin activity is abnormally increased during PAN-induced podocyte injury, whereas the expression of the full-length 60-kDa calcineurin protein is down-regulated due to over-activated calpain that cleaves calcineurin to form a 45-kDa fragment.